Analysis of Business Communication Strategies in Marketing Systems Through Digital Marketing Technology On Today's MSME Actors - Mustari, Mustari; Sirajuddin, Andi Muchlis; Putrawan, Muh. Rizah (Cita konsultindo, 2024)
This study aims to analyze business communication strategies in the marketing system implemented by Micro, Small, and Medium Enterprises (MSMEs) by utilizing digital marketing technology. Through a qualitative approach, the study collected data from a variety of sources, including in-depth interviews with MSME actors, analysis of social media content, and online surveys. The results of the study show that the use of effective digital marketing strategies, such as social media marketing, and email marketing, can increase customer visibility and engagement. In addition, collaboration with influencers and the use of data analytics are key in understanding consumer behavior and improving customer experience. This study concludes that the integration of the right business communication strategy through digital marketing technology can have a significant positive impact on the growth and sustainability of MSMEs.